2016
DOI: 10.3109/0284186x.2016.1155738
|View full text |Cite
|
Sign up to set email alerts
|

Risk of chemotherapy-induced amenorrhea in patients with breast cancer: a systematic review and meta-analysis

Abstract: Background: The aim of the study was to calculate the rate of chemotherapy-induced amenorrhea (CIA) after treatment with different adjuvant therapies in patients with breast cancer and to evaluate the risk factors for CIA based on the quality of evidence. Patient and methods: A search of PubMed and ISI Web of Science was performed. All published trials with female breast cancer patients who received adjuvant chemotherapy and presented data on the rate of CIA were considered eligible. The pooled rates of CIA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 30 publications
(32 reference statements)
5
50
1
7
Order By: Relevance
“…shown that women over 40 years were more likely to present a chemotherapy-induced amenorrhea than women under 40 years regardless of the type of treatment received [4] [11] [12]. This difference in risk was found in our study.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…shown that women over 40 years were more likely to present a chemotherapy-induced amenorrhea than women under 40 years regardless of the type of treatment received [4] [11] [12]. This difference in risk was found in our study.…”
Section: Discussionsupporting
confidence: 64%
“…The definition of chemotherapy-induced amenorrhea varies depending on the study, constituting a limit to the comparison with different studies [10]. Indeed, some authors define the chemotherapy-induced amenorrhea in referring to the end of chemotherapy, while others consider a certain delay from the start of the chemotherapy [4]. We have retained the three-month period by referring to the definition of secondary amenorrhea, which is the absence of menses for more than three months in a woman who has normal menses previously [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that 2 risk factors were associated with the occurrence of CIA supported by a strong level of evidence: older age (>40 years old) and the use of tamoxifen. As for the definition of CIM, Zavos and Valachis [28] explained that a uniform definition of CIA is essential in future studies to make the interpretation of results more reliable. Indeed in the 75 studies selected, 19 different definitions of CIA have been used.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, many studies were able to show that chemotherapy plus tamoxifen lead to an onset of amenorrhea but not to an onset of menopause. Zavos and Valachis [28] examined 75 relevant studies concerning CIA and the risk factors. They demonstrated that 2 risk factors were associated with the occurrence of CIA supported by a strong level of evidence: older age (>40 years old) and the use of tamoxifen.…”
Section: Discussionmentioning
confidence: 99%